PEMBINAAN ANCAMAN HUKUMAN PENYALAHGUNAAN NARKOTIKA DI MADRASAH ALIYAH DARUL IHSAN TANJUNG SENGKUANG KOTA BATAM - Zuhdi Arman; Michael Jibrael Rorong; Irene Svinarky (ASOSIASI IDEBAHASA KEPRI, 2021)
The spread of drugs in Indonesia, which is increasing every year, is increasing by the large population of Indonesia's population. Indonesia is one of the extraordinary markets for drug mafia to bring these illegal goods into the archipelago. The largest number of drug users in Indonesia from year to year are still dominated by students, in this case students and school children, especially high school and junior high school levels. In the medical world, drugs can be medicinal properties for healing. Drug use in the medical world is legal. So what becomes a policeman is when someone consumes drugs without the supervision of a health professional or doctor. If someone uses drugs without the supervision of a doctor, they think it will be very dangerous because drug users are because drugs are poisonous substances that can cause drug users to always depend or be addicted to these drugs, damage organs, affect a person's decline or make thoughts do not become irrational and damage the brain permanently. The result is even more terrible, which leads to death. The abuse of narcotics and illicit drugs among the younger generation is increasing. The proliferation of deviant behavior of the young generation can endanger the survival of this nation in the future. Because youth, as the generation expected to become the nation's successor, are increasingly vulnerable to being eaten away by nerve-destroying addictive substances. So that the young man could not think clearly. As a result, the generation of hope for a nation that is strong and intelligent will only be a memory. The target for the spread of these drugs is young people or teenagers.